Antibacterial Activity Test of Ethanol Extract and SAP of Betung Bamboo Shoot (Dendrocalamus asper) Against Klebsiella pneumoniae and Pseudomonas aeruginosa Bacteria - Anif Nur Artanti; Farikatul Sufi Mujahidah (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
Boiled water from bamboo shoots is often used for pneumonia and a cleanser for the wound. It is known that bamboo can be an antibacterial agent because it has saponin, alkaloid, and flavonoid. This research aims to study whether ethanol extract and sap from bamboo betung shoot (Dendrocalamus asper) has secondary metabolism and antibacterial activity against Klebsiella pneumoniae and Pseudomonas aeruginosa. The extract was taken by maceration method using ethanol 96%, and the sap was taken from the water of bamboo shoot. Antibacterial activity test was conducted using disc diffusion method to measure the magnitude of inhibitory power at six concentration ratios of b/v solutions (10%; 20%; 30%; 40%; 50%; 60%). The result showed that ethanol extract and sap of bamboo betung shoot contained saponin, quercetin, and quinine which were supposed to have antibacterial activity against Klebsiella pneumoniae and Pseudomonas aeruginosa. The largest inhibitory zone diameter was found in ethanol extract 60% with the category of moderate inhibition of 9.05 ± 0.12 mm against Kliebsiella pneumoniae and 5.07 ± 0.13 mm against Pseudomonas aeruginosa. While the sap with a concentration of 60% was included in the weak inhibitory category, which was 5.65 ± 0.05 mm in the Kliebsiella pneumoniae and 4.81 ± 0.22 mm in Pseudomonas aeruginosa. Keywords: antibacterial; bamboo shoot; betung bamboo.